PENGARUH KECEPATAN POTONG TERHADAP TEMPERATUR PEMOTONGAN PADA PROSES PEMBUBUTAN - Steven Moses Lukas Gambeh; Rudy Poeng; Irvan Raymon Rondonuwu (JURNAL POROS TEKNIK MESIN UNSRAT, 2015)
ABSTRACT This research was to find the cutting speed differences which significantly affect the temperature of turning. A testing by turning the lathe by using different rotation, depth of cut and feeding movement were executed. The results of this research shows that by increasing the cutting speed of the turning then the cutting speed temperature will increase. While with a 95% confidence level, it was found that the cutting speed does not affect the temperature of the tools chips and workpiece. Thus the 4461 J/minutes heat generated does not lead to a wear of tools and life time still high. Keyword: Cutting Speed, Turning, Cutting Temperature